FORMING OF THE SKILL OF MODELING TRANSLATION ACTIVITIES AS A NECESSARY COMPONENT OF A FUTURE TRANSLATOR'S PROFESSIONAL COMPETENCE - Vladislava A. Vikhlyaeva (Russian Journal of Education and Psychology)
Background. During the study, it was noted the requirements for the professional competence of future translators and it was mentioned about the importance of the ability to model the translation process for a future specialist. The term "modeling of translation activity" is studied, several translation models existing in translation studies are discussed, their characteristics are given and the features of their practical application are described. The article discusses the methodology of conducting a practical lesson on the practice of translation, which will contribute to the formation of professional competence of future translators, form the connection between theoretical knowledge and practical skills among students, and form a conscious approach to performing translation tasks. Examples of tasks for the practical use of semantic, situational, transformational, communicative, informative, transformational, psycholinguistic models of translation in practical classes on the practice of translation are given. The application of this technology has been tested in practice and it has been indicated the effectiveness of focusing on the use of a particular translation model for translating texts of different genre and style.